Penggunaan Media Pembelajaran Pendidikan Agama Islam Di Sekolah Dasar - Supardi, Herin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Learning is a complex and lifelong process that occurs through individual interaction with the environment. This interaction involves various elements, such as students, teachers, principals, teaching materials, and learning resources and facilities. The development of science and technology requires updates in the use of technology in the learning process. Teachers are expected to be able to use various available learning media, as well as have the skills to develop media if the required media is not yet available. In the context of Islamic Religious Education (IRE), the use of learning media is influenced by several factors, including the teacher's educational background, teaching experience, professional education and training, and the availability of facilities. This study used a descriptive qualitative research method with data collection techniques in the form of observation, interviews, and documentation. This method was used to gain an in-depth understanding of the factors that influence teachers' use of PAI learning media. The results of the study show that teacher competence, professional experience, and facility support are the main determinants of the effectiveness of learning media use. Thus, improving teachers' ability to utilize and develop learning media is essential to support a more optimal PAI learning process.